Capital Structure and Factors Affecting Capital Structure - BHADRAPPA HARALAYYA; Jeelan Basha V; Nitesh S Vibhute (Journal of Advanced Research in Economics and Business Management, 2022)
Capital structure decisions are perhaps one of the most important decisions taken by financial managers. It is one of the important and challenging issues in corporate finance. What should be the appropriate mix of debt and equity in capital structure. The answer to this question has been debated in different literatures pertaining to capital structure by different researchers. The enormous work in this area by different researchers has tried to investigate of optimal capital structure exists or not, which will help in maximization of the wealth of the shareholders. The optimal mix of debt and equity in capital structure will help in maximization the returns for the shareholders, while minimizing the cost of capital. Decisions relating to optimal combination of debt and equity have always raised the inquisitiveness of different researchers all over the globe.